Promoting Internal Armed Conflict Resolution and Peacebuilding: The Case of the US–Colombia Relations (Part I) - A. A. Manukhin (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
In recent years the issues of peaceful resolution of internal armed conflicts and post-conflict reconstruction have increasingly attracted attention of both the leading states and international organizations and the academic community. Researchers agree that it is the identification and elimination of the underlying causes and triggers of conflict that represent one of the major challenges to the states emerging from the internal armed conflicts. The challenge is all the more complex when the internal conflict is internationalized and involves some external actors. In that regard the case of Colombia is of special interest. The paper covers a relatively long period — from mid-1960s to the end of 2000s — and examines the key stages and areas of the United States-Colombia cooperation aimed at the cessation of hostilities in the latter. The paper identifies the underlying causes of the armed conflict in Colombia, its key participants and their goals. The author shows that the forms and the scope of the U.S. assistance to the Colombian government were strongly linked to the evolution of both the situation in that country and the strategic priorities of the US foreign policy in general. While initially the US assistance was determined by the desire to counter the growing influence of the leftist parties and movements in the region, the prioritization of the fight against drug trafficking in the national security strategy in the 1980s resulted in the re-orientation of the US regional policies to the war on drugs. The adoption of the Plan Colombia served as a milestone in the development of the bilateral relations. The paper examines in detail the consequences and results of implementation of this plan. The beginning of the 2000s was yet another pivotal point in the development of bilateral interaction aimed at cessation of hostilities, marked by the 9/11 terrorist attacks, the failure of negotiations between the Colombian government and the opposition, and the implementation of a ‘democratic security’ policy. All this contributed to the convergence of the two governments’ views on security issues and conflict resolution. A new modus vivendi emerged as bilateral partnership was transforming into strategic alliance. However, the author emphasizes, that implications of these new developments on the peace process were yet to be discovered.